2020
DOI: 10.22270/ujpr.v5i4.439
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Premature Loss of Primary Teeth at the Age of 6-10 Years in Sana'a City, Yemen

Abstract: Background and Objectives: Primary teeth and the integrity of the primary teeth are very important for the normal growth and progress of the occlusal relationships and the dentofacial structures. Premature loss of the primary teeth may lead to the loss of the arch length needed for the eruption of permanent teeth and thus lead to rotation, crowding, and impaction of permanent teeth. This study aimed to determine the prevalence of premature loss of primary teeth among children aged 6-10 years in Sana'a city, Ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
3
2
0
Order By: Relevance
“…The results of the present study found that the rates between the genders were similar, which is in accordance with the results of previous studies. [15][16][17] Differences in early loss were detected in different age groups and the highest occurrence was recorded in children of around 8 and 9 years old, in accordance with the findings reported in previous studies. 8,[15][16][17] At least one tooth was diagnosed as requiring extraction in 31% of the patients who attended the clinic, which is consistent with studies conducted by researchers in developing countries.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results of the present study found that the rates between the genders were similar, which is in accordance with the results of previous studies. [15][16][17] Differences in early loss were detected in different age groups and the highest occurrence was recorded in children of around 8 and 9 years old, in accordance with the findings reported in previous studies. 8,[15][16][17] At least one tooth was diagnosed as requiring extraction in 31% of the patients who attended the clinic, which is consistent with studies conducted by researchers in developing countries.…”
Section: Discussionsupporting
confidence: 90%
“…[15][16][17] Differences in early loss were detected in different age groups and the highest occurrence was recorded in children of around 8 and 9 years old, in accordance with the findings reported in previous studies. 8,[15][16][17] At least one tooth was diagnosed as requiring extraction in 31% of the patients who attended the clinic, which is consistent with studies conducted by researchers in developing countries. 17,18 In primary and mixed dentition, the indications for tooth extraction due to caries are 16.6% and 31.2%, respectively.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Early or premature loss is the term for primary tooth loss before the period of its natural exfoliation and it can lead to variety of problems, including crowding, rotation, and impaction of the permanent teeth, formation of crossbites, differences in the median line of teeth, and supra-eruption of the antagonistic teeth; due to drifting of teeth present mesial and distal to the space, which eventually shortens the arch length required for the succeeding teeth. Additionally, it negatively affects children's emotional health and quality of life [3][4][5] . With the intent of preventing malocclusion brought on by the early loss of primary teeth, space maintainers can be employed, depending upon the child's dental development stage, the affected dental arch, the missing primary teeth [4,6] .…”
Section: Introductionmentioning
confidence: 99%
“…Investigation and survey of dental health problems in Yemen are in spite of everything fairly small and limited, even though there were studies that dealt with the problems of dental caries, the prevalence and pattern of third molar impaction in adults and children, periodontal infections, and causes of extraction of permanent teeth [1][2][3][4][5][6][7][8], however no exploration converge the prevalence of premature loss of primary teeth and its effect on malocclusion. Early loss of primary teeth is a worldwide problem.…”
Section: Introductionmentioning
confidence: 99%